DRAMATIC ART OF SI DALUPA DATOK RIMBA ART STUDIES IN WEST ACEH - Susandro Susandro (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
The traditional art of Si Dalupa produced by the Datok Rimba Art Studio can be categorized as theatrical art based on the form of the work and especially because of its supporting elements; scriptwriter, director, actor, and musician. Apart from that, the art is also worked out cinematically. This article aims to analyze the drama of Si Dalupa's art in cinematic form based on the ideas of George R. Kernodle called 'structure' and 'texture'. The structure consists of themes, plots, characterizations. Meanwhile, texture covers dialogue, atmosphere, and spectacle. This research approach is qualitative with literature study techniques, observation, in-depth interviews, and documentation. As a result, in terms of structure, Si Dalupa's art has the theme of the arrival of Islam to Aceh, the storyline is linear. Each character has a diverse physique, character, and social background. Whereas in terms of texture, each actor uses the Acehnese language, the atmosphere is built with serune and rapa'i musical instruments. Meanwhile, the spectacle is set in a forest and residential areasKeywords: Si Dalupa; Dramatic Elements; Cinematic DRAMATIKA KESENIAN SI DALUPA SANGGAR SENI DATOK RIMBA DI ACEH BARATAbstrakKesenian tradisional Si Dalupa produksi Sanggar Seni Datok Rimba dapat dikategorikan sebagai seni teater berdasarkan bentuk karya dan terutama karena unsur pendukungnya; penulis naskah, sutradara, aktor, dan pemusik. Selain itu, kesenian tersebut juga digarap secara sinematik. Artikel ini bertujuan menganalisis dramatika kesenian Si Dalupa dalam bentuk sinematik berlandaskan pada gagasan George R. Kernodle yang disebut ‘struktur’ dan ‘tekstur’. Struktur terdiri dari tema, alur, penokohan. Sedangkan tekstur melingkupi dialog, suasana, dan spektakel. Pendekatan penelitian ini ialah kualitatif dengan teknik studi pustaka, observasi, wawancara mendalam, dan dokumentasi. Hasilnya, pada struktur, kesenian Si Dalupa bertemakan ikhwal masuknya Islam ke Aceh, alur ceritanya linear. Setiap tokoh memiliki fisik, watak, dan latar sosial yang beragam. Sedangkan pada tekstur, setiap pemeran menggunakan bahasa Aceh, suasana dibangun dengan alat musik serune dan rapa’i. Sedangkan spektakelnya berlatar hutan dan pemukiman warga.Kata Kunci: Si Dalupa; Unsur Dramatik; Sinematik